2011
DOI: 10.1111/j.1365-294x.2011.05330.x
|View full text |Cite
|
Sign up to set email alerts
|

Testing the effect of transient Plio-Pleistocene barriers in monsoonal Australo-Papua: did mangrove habitats maintain genetic connectivity in the Black Butcherbird?

Abstract: Changes in climate and sea level are hypothesized to have promoted the diversification of biota in monsoonal Australia and New Guinea by causing repeated range disjunctions and restricting gene flow between isolated populations. Using a multilocus (one mtDNA locus, five nuclear introns) phylogeographic approach, we test whether populations of the mangrove and rainforest restricted Black Butcherbird (Cracticus quoyi) have diverged across several geographic barriers defined a priori for this region. Phylogeograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
52
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 70 publications
9
52
0
Order By: Relevance
“…Early sequencebased phylogeographic studies in babblers [Pomatostomus (58)] reported deep divergence across the CB relative to divergence within the eastern and western regions of the continent. Subsequent multilocus analyses of several avian systems revealed mostly Pleistocene divergences across the CB for congeners (59)(60)(61), as well as within species (62,63). Some studies examining divergence across the region have discovered clines (64) or complex reticulate patterns in the form of introgression; for example, in butcherbirds (Cracticus), populations east of the KTEB are introgressed with mtDNA from populations of arid-adapted species to the south that expanded during the last glacial maximum, whereas populations west of the KTEB are not introgressed (65).…”
Section: Key Processes Of Divergence and Reticulation In Naturementioning
confidence: 99%
“…Early sequencebased phylogeographic studies in babblers [Pomatostomus (58)] reported deep divergence across the CB relative to divergence within the eastern and western regions of the continent. Subsequent multilocus analyses of several avian systems revealed mostly Pleistocene divergences across the CB for congeners (59)(60)(61), as well as within species (62,63). Some studies examining divergence across the region have discovered clines (64) or complex reticulate patterns in the form of introgression; for example, in butcherbirds (Cracticus), populations east of the KTEB are introgressed with mtDNA from populations of arid-adapted species to the south that expanded during the last glacial maximum, whereas populations west of the KTEB are not introgressed (65).…”
Section: Key Processes Of Divergence and Reticulation In Naturementioning
confidence: 99%
“…Many studies have highlighted the importance of the Carpentarian barrier in shaping species distribution and diversification (Cracraft 1986; Cardinal and Christidis 2000; Jennings and Edwards 2005; Lee and Edwards 2008; Kearns et al. 2011). However, phylogeographic studies of birds have shown contradictory patterns across the Carpentarian barrier: strong differentiation (Lee and Edwards 2008; Toon et al.…”
Section: Discussionmentioning
confidence: 99%
“…2010; Kearns et al. 2011) and the apparent absence of any impact on species differentiation (Kearns et al. 2010; Joseph et al.…”
Section: Discussionmentioning
confidence: 99%
“…Phylogeographic studies of the Australian Magpie C. tibicen (Toon et al, 2007), the Pied Butcherbird C. nigrogularis (Kearns et al, 2010) and the Black Butcherbird C. quoyi (Kearns et al, 2011) have provided compelling evidence that cyclic aridity during the Pleistocene likely caused range contractions and vicariance across regions of unfavourably arid habitats in these species (see also Byrne et al, 2008). Critically, however, the influence of earlier phases of aridity and changes in landscape have not been tested in the Australo-Papuan butcherbirds and allies.…”
Section: Introductionmentioning
confidence: 97%